La Niña Impacts on Austral Summer Extremely High-Streamflow Events of the Paranaíba River in Brazil - Netrananda Sahu; R.B. Singh; Pankaj Kumar; Roberto Valmir Da Silva; Swadhin K. Behera (Advances in Meteorology)
The extremely high-streamflow events of the Paranaíba River basin are found to be associated with La Niña phenomenon during December–February (DJF). Extreme events are identified based on their persistent flow for seven days and more after taking retention time into consideration. The extremely high-streamflow events are associated with the La Niña years; 80% of the high-streamflow events have occurred during La Niña phases. Therefore, a very-significant 80% and above correspondence of the La Niña events and the seasonal streamflow anomalies are found in DJF. Although climate variations have direct relationship with the rainfall, streamflow variations are considered as the surrogates to rainfalls. However, apart from climate variations the anthropogenic and land-use changes also influence streamflow variations. In this study, we have applied multivelocity TOPMODEL approach and residual trend analysis to examine the impact of land-use to the streamflow at the Fazenda Santa Maria gauge stations. However, the model residual trend analysis of the TOPMODEL approach cannot quantify the extent of land-use impact. Thus, La Niña phase is important components to understand and predict the streamflow variations in the Paranaíba River basin.